ART THERAPY IN CHANGING THE CULTURAL CONDUCT OF CHILDREN OF THE MILINEAL ERA - Andi Imrah Dewi; Andi Ardiansyah; Henriana Sri Rejeki; Erniati (Universitas Tadulako, 2021)
Changes in children's behavior are the things that parents can most closely observe, when children feel happy and comfortable or are sad. However, what is most highlighted in this condition is in-depth observation of case studies experienced by students due to dependence on the use of technology. The huge demands of the current conditions that require them to communicate with cellphones and other media that blend in electronics make communication with parents actually neglected. From the results of their survey there is a tendency to contact more with various applications that are complete in exploring cyberspace and this becomes the biggest problem as well as the challenge for parents in educating their children. So that the results that we will achieve in this study are: there is providing reinforcement or a separate solution to parents by inviting their children to get to know the social and natural environment through thought therapy that can provide their own stimulation for their children, one of which is by trapi through the art of inviting children to color, draw or dance all of that is a solution. To be able to control themselves by adopting various approaches and directions that are even better in meeting the needs, communication, closeness and attention of their parents is needed for the continuation of the life of the passenger generation which of course must be accompanied by faith and piety as a barometer in controlling children so that does not dissolve in mere pleasures of the world.